Scope and experience in influencing the organizational commitment of employees True Corporation Public Company Limited (Thailand) - Tunhakorn, Tibdi; Jesadaelux, Wiroj (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This study purpose is to study and work experience in influencing the organizational commitment of True Corporation Public Company Limited (Thailand) of 310 people. The tools used in this study was a questionnaire validated by content experts. And check the validity of using Cronbach’s alpha coefficient. Data were analyzed by using frequency, percentage standard deviation. The coefficient of Pearson. Simple regression analysis and Multiple regression analysis The results showed that job. Experience and organizational commitment at a high level. Job and work experience have a positive influence on organizational commitment of employees. The study results will be made official company executives can define, develop and plan the job. Work experience and policy makers to build organizational commitment to staff up and remain in the organization forever. Article history : Accepted 31 May 2016 SIMILARITY INDEX = 0.00